PEMBERDAYAAN MASYARAKAT PASCA BENCANA ERUPSI GUNUNG SINABUNG DI RELOKASI SIOSAR KABUPATEN KARO - Agung Kacaribu; Adianto Adianto (Universitas Halu Oleo, 2022)
Mount Sinabung is one of two mountains that have been designated as active in Karo Regency so far. When an eruption occurs, it will cause a lot of damage and loss. In restoring it, the provision of assistance to the community and community empowerment efforts after the eruption of Mount Sinabung were carried out in three ways, namely, creating an atmosphere or climate that allows the potential of the community to develop, strengthening the potential or power of the community (empowering), and protecting and defending the interests of the weak. so as not to get weaker. Efforts to empower the community after the eruption of Mount Sinabung were carried out in three methods, namely, creating an atmosphere or climate that allows the potential of the community to develop, strengthening the capabilities or potentials of the community (empowering), and protecting and defending the interests of the weak so as not to get weaker. This research uses a qualitative type of research with a descriptive case study approach in order to describe cases in the field and share answers to cases encountered. The results of this study found that community empowerment after the eruption of Mount Sinabung in the relocation of Siosar, Karo Regency had increased. This is due to the three stages of community empowerment that exist, the community in the Siosar relocation area has a large level of empowerment in the process of creating an atmosphere or climate that allows the potential of the community to develop and efforts to protect and defend the interests of the weak so as not to be weak, on the contrary in the process of strengthening the capacity of the community. or the potential of the community is still not maximized. In addition, there are factors that limit community empowerment, such as the low level of community understanding and the lack of facilities and infrastructure.